1996
DOI: 10.1111/j.1528-1157.1996.tb00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism in Temporal Lobe Epilepsy: Assessment and Implications for Pre‐ and Postoperative Psychosocial Adjustment and Health‐Related Quality of Life

Abstract: We assessed 77 candidates for epilepsy surgery to determine the association among neuroticism (a dimension of personality characterized by chronic negative emotions and behaviors), psychosocial adjustment as measured by the Washington Psychosocial Seizure Inventory (WPSI), and health-related quality of life (HRQOL) as measured by the Epilepsy Surgery Inventory 55 (ESI-55). Minnesota Multiphasic Personality Inventory 2 (MMPI-2) Neuroticism scale scores were significantly correlated with many domains of patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 41 publications
1
20
0
3
Order By: Relevance
“…Neuroticism has been reported as the best predictor of general well-being irrespective of seizure frequency in preoperative and postoperative populations of patients with epilepsy (22,29). Hence, its influence on the patient's subjective perception is noteworthy, and although actual memory impairment does exist, person-S. CMIZARES ET AL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroticism has been reported as the best predictor of general well-being irrespective of seizure frequency in preoperative and postoperative populations of patients with epilepsy (22,29). Hence, its influence on the patient's subjective perception is noteworthy, and although actual memory impairment does exist, person-S. CMIZARES ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroticism is defined as being prone to a chronic dysphoric mood, instability, and a specific vulnerability to negative affective states (27,28). Neuroticism has been negatively related to several variables in quality-of-life research in epilepsy (22,29). It also correlates with subjective memory complaints in patients with refractory epilepsy (5).…”
mentioning
confidence: 99%
“…It may cause a response bias in overreporting of negative symptoms and a decreased self-assessment of QOL. A negative affect that includes high degrees of anxiety may present a surgery-associated risk factor because these tendencies seem to get worse after surgery regardless of the surgical outcome (13). Indeed, these patients are often in need of psychotherapy after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, self-report can reflect bias, for example, exaggeration or diminution of symptoms (10). It has been suggested that mood states, particularly that of depression, influence patients' perceptions and self-reporting of cognitive status (11)(12)(13). In these studies, increased complaints of problems with memory have been associated with abnormalities of the mood state.…”
mentioning
confidence: 89%
“…A QV sofre influência de vários fatores relacionados a: estratégias de adaptação psicossocial 10 , traços de personalidade do indivíduo 11 , sua história e expectativas em relação a vida 12 , seu auto-conceito 10 e auto-eficiência 13 , suporte social que recebe das pessoas que lhe são significativas 13 , seu locus de controle 10-13-14-15 e percepção de controle de crises. Dentre estes fatores, esta última foi a variável subjetiva pesquisada neste estudo.…”
Section: Discussionunclassified